Protest policing and policing protesters: litigation in the U.S. circuit courts of appeals - Kondrat, Allison G. (Crime, law and social change, 2024)
After the surge in political protests during the summer of 2020, protest rights have been thrust into the forefront of the nation’s consciousness. Specifically, questions have arisen with respect to the boundaries of the First Amendment rights of protesters, in addition to the duty of police officers to maintain public safety and order. In this article, the interpretation and application of relevant First Amendment precedents involving protest policing and the policing of protesters are examined using cases decided by the United States Circuit Courts of Appeals. Using inductive, qualitative doctrinal methods in the tradition of grounded theory, four overarching themes emerged among the caselaw: place of protest, protest permits, law enforcement misconduct, and ordinances that restrict protests. Findings from the court rulings emphasize the importance of supervision of law enforcement and adequate training of officers who police protests. While order maintenance and public safety remain critical, law enforcement must internalize the importance of their role in protecting the First Amendment right to protest.